1975
DOI: 10.1111/j.1445-5994.1975.tb03269.x
|View full text |Cite
|
Sign up to set email alerts
|

Diarrhoea and Colitis Associated with Antibiotic Treatment: A Report of 16 cases

Abstract: Sixteen cases of colitis developing within twenty-one days of antibiotic therapy are reported. There was a wide range of disease severity. Lincomycin and Clindamycin were implicated in twelve. The colitis was of two pathological patterns pseudomembranous colitis and "non-specific" colitis. There is a relative sparing of the rectum in some cases making the diagnosis more difficult on sigmoidoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

1977
1977
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…3), is the earliest recognisable abnormality on which to make a positive diagnosis of pseudomembranous colitis. It is well illustrated in other papers and is not simply an artefact of sectioning (as serial sections in this study have shown) Gibson et al, 1975;Steer, 1975). It occurs immediately beneath the surface epithelium between the glandular openings.…”
Section: Histopathologysupporting
confidence: 77%
See 1 more Smart Citation
“…3), is the earliest recognisable abnormality on which to make a positive diagnosis of pseudomembranous colitis. It is well illustrated in other papers and is not simply an artefact of sectioning (as serial sections in this study have shown) Gibson et al, 1975;Steer, 1975). It occurs immediately beneath the surface epithelium between the glandular openings.…”
Section: Histopathologysupporting
confidence: 77%
“…It is questionable whether all 'antibiotic induced (Gibson et al, 1975). If one excludes proven infective lesions, such as staphylococcal colitis, it is possible that this is the case.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…It is well established that certain patients who receive antibiotics develop diarrhoea (Tedesco, 1975); it is not known if there are any mucosal abnormalities at this stage. A minority of patients in this 'susceptible' state go on to develop a definite colitis which is either nonspecific or pseudomembranous in type (Gibson et al, 1975). It is in the latter group that C. difficile is found in the gut.…”
Section: Discussionmentioning
confidence: 99%
“…Until 1970, only a few publications discussed the surgical management of C. difficile disease, and diversion was commonly used [73,79,108,182,184,[186][187][188][189][190]. This Surgical Treatment Indications for surgery include complicated or severe resulted in a high mortality rate of 66% since the diseased organ was not removed [17].…”
Section: Medical Treatmentmentioning
confidence: 99%